Evaluation of direct torque control with a constant-frequency torque regulator under various discrete interleaving carriers - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (Electronics (Switzerland), 2019)
Constant-frequency torque regulator-based direct torque control (CFTR-DTC) provides an attractive and powerful control strategy for induction and permanent-magnet motors. However, this scheme has two major issues: A sector-flux droop at low speed and poor torque dynamic performance. To improve the performance of this control method, interleaving triangular carriers are used to replace the single carrier in the CFTR controller to increase the duty voltage cycles and reduce the flux droop. However, this method causes an increase in the motor torque ripple. Hence, in this work, different discrete steps when generating the interleaving carriers in CFTR-DTC of an induction machine are compared. The comparison involves the investigation of the torque dynamic performance and torque and stator flux ripples. The effectiveness of the proposed CFTR-DTC with various discrete interleaving-carriers is validated through simulation and experimental results.
Keywords: Constant-frequency torque regulator; Direct torque control; Flux regulation; Induction motor; Interleaving carriers; Low-speed operation